Case report: Bilateral optic nerve sheath meningocele: clinical aspects - Catalán-Coronado, Saray; Parrado-Carrillo, Alba; Nogués-Castell, Javier; Rosinés-Fonoll, Josep; Camós-Carreras, Anna; Alcubierre, Rafel; Carrión-Donderis, Maria Teresa; Bernal-Morales, Carolina; Sánchez-Dalmau, Bernardo (Frontiers in Ophthalmology, 2024)
Optic nerve sheath meningocele is an enlargement of the sheath itself, consisting of a collection of cerebrospinal fluid along the perineural space. It should be considered primary if it is not associated with orbital–cerebral neoplasm or with cranio-orbital junction malformations. We report three cases of bilateral primary idiopathic optic nerve sheath meningocele, two of them with gradual vision loss. The first case presented a history of monocular blurred vision of the right eye and headache. It was initially treated with acetazolamide without any improvement, after which optic nerve sheath fenestration was required. The second case showed intermittent binocular diplopia with central 24-2 perimetry defects in the left eye. The third case was first presented as a subacute bilateral conjunctivitis with a suspected orbital pseudotumor. An incidental bilateral optic nerve sheath meningocele was found in the orbital imaging, being totally asymptomatic. In all the cases, orbital and cranial magnetic resonance with contrast and fat suppression was crucial in the diagnosis.